The Significance of Mediator Certificate for Village Heads in Dispute Resolution - Syahrul Ibad; Ainun Najib; Ummassahda Ummassahda; Marco Rizzi (Universitas Lampung, 2025)
Humans are social beings whose interactions often generate conflicts arising from differing interests. Dispute resolution may be pursued through litigation or non-litigation mechanisms, including mediation. This study examines village-level mediation conducted by Kepala Desa (village head), which is rooted in local wisdom and community practices, and mandated by Law Number 6 of 2014 concerning Villages, Article 26 paragraph (4), requiring Kepala Desa to resolve community disputes. The findings indicate that mediator certification is urgently needed to enhance the effectiveness of Kepala Desa in dispute resolution and to improve efficiency in terms of cost, time, and access to justice. Although mediation outcomes are binding and have evidentiary value for the parties, they do not possess Permanent legal force equivalent to a final court decision unless elevated to a peace deed (akta perdamaian).